What makes people feel poor when they are economically non-poor? Investigating the role of intergenerational mobility and comparison with friends. (October 2021) - Peng, Chenhong
Highlights: Intergenerational mobility affects the discrepancy between people's economic poverty status and their perceptions of poverty status. Social comparison with one's friends affects the discrepancy between people's economic poverty status and their perceptions of poverty status. Parents appear to be a more important reference group than friends in shaping the mismatch between economic and subjective poverty. Abstract: This study examines how comparisons with "close others, " namely, parents and friends, influence the discrepancy between economic and subjective poverty. Comparison with parents reflects "intergenerational mobility" and "equality of opportunity, " whereas comparison with friends reflects "equality of outcome." The data were drawn from the first wave of the Hong Kong Panel Survey for Poverty Alleviation ( N = 2000). As suggested by the theories of fulfilled aspiration, falling-from-grace, self-serving bias and self-interest, I found that people who had experienced upward intergenerational mobility were more likely to feel non-poor even if they were economically poor, and that people who had experienced downward intergenerational mobility were more likely to feel poor even if they were economically non-poor. This association was found for subjective, but not for objective, measures of intergenerational mobility. When comparing themselves to friends, people made both downward and upward comparisons. As suggested by social comparison theory, those who contrasted their social status with their lower-status friends were more likely to feel non-poor, even if they were economically poor, whereas people who contrasted their social status with their higher-status friends were more likely to feel poor even if they were economically non-poor. Moreover, when considering both parents and friends as reference groups, I found that parents (equality of opportunity) appeared to be a more important reference group than friends (equality of outcome).